Enhanced treatment of dispersed dye-production wastewater by self-assembled organobentonite in a one-step process with poly-aluminium chloride - Liu, Yao; Zhu, Lizhong (Scientific reports, 2017)
Organobentonite has been successfully applied in industrial wastewater treatment. However, the solid-liquid separation in wastewater treatment still needs improvement. This study presents an enhanced approach with high removal efficiency and short separation time for dispersed dye-production wastewater using self-assembled organobentonite in a one-step process with poly-aluminium chloride (PAC). The enhanced effects of PAC on wastewater treatment by organobentonite were comprehensively evaluated. Following the primary decontamination by the self-assembled organobentonite, the removal efficiency for dispersed dye-production wastewater was strengthened with PAC coagulation. The removal rates of TOC and organic pollutants were 55.0% and 63.5%, respectively, with the PAC-enhanced approach and were 1.3- and 1.6-fold higher, respectively, than those with the self-assembled organobentonite approach. The combination of PAC with self-assembled organobentonite was able to break the stability of the organobentonite suspension and enlarge the floc size, and thus reduce the solid-liquid separation time from 30 min to 10 min. Additionally, this enhanced approach could improve the biodegradability of wastewater with the BOD 5 /COD Cr ratio increasing from 0.22 to 0.39, which was 4.1-fold higher than that of only organobentonite in a one-step process. Therefore, the PAC-enhanced approach could be a promising technology for wastewater pretreatment in practical industrial applications.